KONTRIBUSI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA SEKOLAH DASARDI ERA REVOLUSI INDUSTRI 4.0 - Alya Cahyani; Siti Masyithoh (STAI Sangatta Kutai Timur, 2023)
Education has a very influential role in shaping the character of students in every era, including in the era of the industrial revolution 4.0. The students’ character education is an important aspect of the implementation of learning in any field. However, this character education must be formed one of them with Islamic religious education, for example carrying out customs in schools, such as congregational Duha prayers, congregational midday prayers, tadarus, and others. The instilling character values ​​as part of the vision, mission, and goals of the institution and trying to make it happen through real activities is one of the strategies that can be applied in developing character education for students. Writing this article aims to determine the formation of students’ character through Islamic religious education in schools. The results showed that the formation of students' character through Islamic religious education was formed by learning aqidah as the basis of religion, learning the Koran and hadith as a way of life and as a legal guide in worship, and learning morals as a guide. guide. for good or bad behavior. Quality education is education that can shape the character of its students. This study concludes that individuals must familiarize themselves with the realization of teachings that are in harmony with Islamic teachings to have a wise personality.